Negosiasi Identitas dalam Dinamika Komunikasi Antara Mahasiswa Penggemar Budaya Populer dengan Budaya Lokal di Universitas Sahid Surakarta - Alya Kurnia Safitri; Ahmaddhany Ahmaddhany; Rachel Melinda; Erwin Kartinawati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The diversity of cultural preferences among students creates interesting communication dynamics in the scope of friendship on campus. Using descriptive qualitative research with an ethnographic approach, this study aims to find out how students who are fans of popular culture (Korean and Japanese) and local culture (Javanese) negotiate their cultural identity. Through participatory observation and interviews conducted with three informants, the results showed the existence of openness, adaptation, and the tendency of functional biculturalism. So that intercultural communication can take place harmoniously and support the formation of a flexible multicultural identity.